2020
DOI: 10.1038/s41467-020-15657-3
|View full text |Cite
|
Sign up to set email alerts
|

Genomic release-recapture experiment in the wild reveals within-generation polygenic selection in stickleback fish

Abstract: How rapidly natural selection sorts genome-wide standing genetic variation during adaptation remains largely unstudied experimentally. Here, we present a genomic release-recapture experiment using paired threespine stickleback fish populations adapted to selectively different lake and stream habitats. First, we use pooled whole-genome sequence data from the original populations to identify hundreds of candidate genome regions likely under divergent selection between these habitats. Next, we generate F2 hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
3
22
1
Order By: Relevance
“…g . Crossley et al 2017, Fritz et al 2018, Nosil et al 2018, Weetman et al 2018, Bi et al 2019, Dayan et al 2019, Laurentino et al 2020). Yet their use for studying pest adaptation to agricultural systems has been limited to a few cases (reviewed in Pélissié et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…g . Crossley et al 2017, Fritz et al 2018, Nosil et al 2018, Weetman et al 2018, Bi et al 2019, Dayan et al 2019, Laurentino et al 2020). Yet their use for studying pest adaptation to agricultural systems has been limited to a few cases (reviewed in Pélissié et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the few cases where reproductive isolation has been demonstrated, it can result either as a by-product of divergent adaptation to different habitats or ecological niches that lead to assortative mating preferences (Rundle et al, 2000;Boughman, 2001), or from ecological selection that puts hybrids at a fitness disadvantage and may lead to reinforcement (Rundle and Schluter, 1998;Lackey and Boughman, 2017). Previous work on crosses of sympatric benthic and limnetic stickleback demonstrated that hybrids are not at any intrinsic disadvantage, but they may perform worse than either of the parental types in the parental niche (Schluter, 1994(Schluter, , 1995(Schluter, , 2003Schluter et al, 1996;Hatfield and Schluter, 1999;Vamosi et al, 2000;Jones et al, 2006;Gow et al, 2007;Arnegard et al, 2014;Laurentino et al, 2020). This opens the possibility that hybrids could invade novel (non-parental) niches if the opportunity arises.…”
Section: How Stickleback Diversifymentioning
confidence: 99%
“…Compared with our database, finding out growth-related functional annotation and molecular mechanisms are both shared in the GH/IGF axis and its downstream signaling pathways. However, these studies have focused on gene function and its integrated signal pathways; by contrast, transcripts identified using a transcriptome profile may influence target traits through various genes [ 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%